SUPPORT AND DEVELOPMENT OF SMALL BUSINESS ENTREPRENEURSHIP IN THE REPUBLIC OF KAZAKHSTAN (Алматы технологиялық университетінің хабаршысы, 2021)
Comprehensive support for small and medium-sized businesses has always been a priority of state policy. This article discusses the important areas of the state economic policy to support and develop small business, to stimulate state support for small business. In the course of an expert survey conducted among professionals directly related to small and medium-sized businesses, it was found that in our country the necessary conditions for the intensive development of small and medium-sized businesses. At the same time, 37.5% of respondents considered these conditions as normal, the same number of respondents said that "there are conditions, but there are some problems", and 18.8% of experts replied: "in General, the main, defining conditions have been created".